2012
DOI: 10.5505/tjtes.2012.48403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urogenital injuries in patients with trauma at the emergency department

Abstract: AMAÇBu çalışmada, ürogenital bölgeyle ilişkili travma nedeniyle acil servise başvuran hastaların özellikleri, morbidite ve mortalite ile ilişkili durumların belirlenmesi amaç-landı. GEREÇ VE YÖNTEMBu prospektif, kesitsel tanımlayıcı çalışmada, ürogenital bölgeyle ilişkili travması olan hastaların demografik özel-likleri, travma şekilleri, inceleme sonuçları, yatış işlemle-ri ve sonuçları değerlendirildi. Çalışmaya toplam 153 majör travması olan hasta [108 erkek (%70,6); 45 (%29,4) kadın] alındı. BULGULAROlgula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 15 publications
1
11
0
5
Order By: Relevance
“…In our country, increased vehicle traffic, increased usage of technological devices in home and work life, increasing violence between individuals increase the number of patients exposed to trauma [4]. In our study, we determined that the number of patients who exposed to urogenital trauma increased in each passing year and there was an increased incidence of urogenital trauma in August and September.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…In our country, increased vehicle traffic, increased usage of technological devices in home and work life, increasing violence between individuals increase the number of patients exposed to trauma [4]. In our study, we determined that the number of patients who exposed to urogenital trauma increased in each passing year and there was an increased incidence of urogenital trauma in August and September.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, we determined that the number of patients who exposed to urogenital trauma increased in each passing year and there was an increased incidence of urogenital trauma in August and September. Büyükcam et al reported that the most common traumatic injuries were seen in July, August and September [4]. Atherton et al [9] reported that the number of trauma patients has increased in the summer months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations